2008
DOI: 10.1002/msc.125
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to change of the Rheumatoid Arthritis Self‐Efficacy scale (RASE) and predictors of change in self‐efficacy

Abstract: The RASE is sensitive to change in a cohort of people with RA in the UK receiving education programmes as routine clinical care. Exploratory analysis did not identify clinical or psychological factors that predict change in SE, suggesting that programmes should not be restricted to particular patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
1
7

Year Published

2010
2010
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 38 publications
3
20
1
7
Order By: Relevance
“…These results match the results from the sensitivity study of the original RASE (Hewlett et al, 2008). Three months after attending the short course, our mean difference (2.27; SD 11.08) matches the three-month results from Bristol (2.09; SD 9.91) (non-published data).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…These results match the results from the sensitivity study of the original RASE (Hewlett et al, 2008). Three months after attending the short course, our mean difference (2.27; SD 11.08) matches the three-month results from Bristol (2.09; SD 9.91) (non-published data).…”
Section: Discussionsupporting
confidence: 93%
“…The distribution of correlation coeffi cients in the item-scale correlations was similar to the fi ndings in the sensitivity study of RASE (Hewlett et al, 2008). In the British sensitivity study, question 7 was found to have a low correlation between question and scale (r = 0.267), so we did not expect it to be higher in RASE-DK (r = 0.212).…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations